Juventude e religião no espaço universitário: cenários das opções religiosas de alunos do curso de pedagogia da Universidade Guarulhos - Prescinotto, Tania Regina Ferri (2010)
This study had as an objective to investigate the Universidade de Guarulhos Pedagogy course student s religious options. The theorical references were based on the Jorge Cláudio Ribeiro and Regina Novaes research, which has contributed for reflection and analysis regarding the youth and their relation with religion. The field research was taken within the Universidade de Guarulhos walls with the Pedagogy course s students from the fifth and sixth semesters. For this study, a quantitative research with closed questions was made. Through the field research it was possible to identify the student s religious options and how do these choices end up interfering within their lives